4 sqrt (32) + 6 sqrt (50)
4 sqrt (16*2) + 6 sqrt (2*25)
4 sqrt (16)*sqrt(2) + 6 sqrt (2)*sqrt(25)
4 *4*sqrt(2)+6sqrt(2)*5
16sqrt(2)+30sqrt(2)
46sqrt(2)
Step-by-step explanation:
See attached picture.
First, compare the highest term of the dividend (x²) to the highest term of the divisor (x). We need to multiply the divisor by x.
When we do that, we get x² + 5x. Subtracting this from the dividend, we get -9x + 11.
Now repeat the process. Compare the highest term of the new dividend (-9x) to the highest term of the divisor (x). We need to multiply by -9.
When we do that, we get -9x − 45. When we subtract from the new dividend, we get 56.
So the quotient is x − 9, and the remainder is 56.
Answer:
x=5 y=-6
Step-by-step explanation:
3x+y=9 ------eqn1
y=4-2x -------eqn2
using substitution
put y=4-2x into eqn1
3x+4-2x=9
x=5
put x=5 into eqn2
y=4-2(5)
y=4-10
y=-6